Огляд та перспективи розвитку матеріалів для контактів електромеханічних апаратів низької напруги - Клименко, Б.В.; Кохановський, В.О. (Електротехніка і електромеханіка, 2011)
The characteristics of materials for contact terminals, as well as the properties and composition of composite materials in the contact elements of the most common types of electromechanical switching devices. Privat-dyatsya data on the new wear resistant and environmentally safe composite contact material.